1989
DOI: 10.1093/oxfordjournals.ndt.a091852
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Membranous Glomerulonephritis: A Prospective Study of 82 Adult Patients

Abstract: Eighty-two consecutive Caucasian adults (52 males, 30 females, aged 17-86 years) with membranous glomerulonephritis were prospectively evaluated for possible aetiological factors 1-4 weeks after renal biopsy. Presumed causes were identified in 17 patients (21%) as follows: drugs in five (D-penicillamine 3, captopril 1, fenoprofen 1); malignancy in four; chronic thyroiditis in three; systemic lupus erythematosus (SLE) in two; secondary syphilis in one; hepatitis B virus (HBV) infection in one and non-insulin-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…Another important point stressed in this previous study was that proteinuria decreased with tumor regression. Similarly, in other previous studies, the prevalence of cancer in patients with MN was reported to be 5-22% (11,12).…”
Section: Discussionsupporting
confidence: 77%
“…Another important point stressed in this previous study was that proteinuria decreased with tumor regression. Similarly, in other previous studies, the prevalence of cancer in patients with MN was reported to be 5-22% (11,12).…”
Section: Discussionsupporting
confidence: 77%
“…It was reported that membranous nephropathy was much less common in the Chinese population than in the white population. [9][10][11][12][13][14] Although both HLA-DQA1 and PLA2R1 are associated with the development of membranous nephropathy in the Chinese population, PLA2R1 gene variance has shown a much stronger association with the development of IMN as well as the production of anti-PLA2R autoantibodies. In this study, we explored other SNPs in HLA-DOB and HLA-DQB2, which showed a relatively strong signal in European GWAS data; however, only HLA-DQA1 was identified as being associated with membranous nephropathy in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In this study, we aim to evaluate the association between these risk alleles and the development of IMN in a large Chinese cohort with .2000 participants and to further explore their roles in the generation of anti-PLA2R antibodies and expression of PLA2R in glomeruli.…”
mentioning
confidence: 99%
“…It usually is idiopathic, and 21% to 25% of cases occur secondary to such identifiable causes as systemic lupus nephritis, malignancies, hepatitis B, and use of drugs. 1 Drugs appear to be the cause of membranous nephropathy in 6% to 9% of cases, and a variety of drugs were reported in association with its development. 1 Gold and penicillamine used in patients with rheumatoid arthritis are typical examples of causative drugs.…”
mentioning
confidence: 99%
“…1 Drugs appear to be the cause of membranous nephropathy in 6% to 9% of cases, and a variety of drugs were reported in association with its development. 1 Gold and penicillamine used in patients with rheumatoid arthritis are typical examples of causative drugs. 2,3 Nonsteroidal anti-inflammatory drugs also were implicated in the development of membranous nephropathy.…”
mentioning
confidence: 99%